IMPLEMEMNTASI NILAI-NILAI ISLAM MODERAT DALAM PEMBELAJARAN AKIDAH AKHLAK PADA MASA PANDEMI DI SDIT AL FALAAH SIMO - Edi Susilo Male; Sukarni F; Muh. Aseffudin M; Raharjo M; Agus Sutiyono M (Balai Diklat Keagamaan Denpasar, 2022)
This qualitative study aims to determine the process of inculcating moderate Islamic values ​​in learning the akidah akhlak at SDIT Al Falaah Boyolali. This research was conducted to answer three questions, namely: (1) What are the moderation values? (2) How is moderation Islamic values ​​embedded during the covid-19 pandemic? (3) What are the implications of cultivating moderation Islamic values ​​during the covid-19 pandemic to prevent radicalism? The subjects of this study were 319 students, 2 teachers of akidah akhlak, the principal and vice principal of curriculum. Data was collected through observation, interviews, and documentation using descriptive analytical techniques. Research informants are teachers of akidah akhlak, the principal, the vice principal of curriculum and students. The results of the study show that (1) the moderation Islamic values ​​instilled include Al-Adl (justice), Al-Tawazun (balance), and At-Tamasuh (tolerance). (2) The process of implanting it integrated with the existing curriculum has been balanced by the creativity of the teacher in inserting the concept of these values ​​from planning to the learning assessment process and (3) The implication of moderation Islamic values ​​is that the behavior of students is good and the results have been shown in their behavior with friends and teachers at school, and behavior with parents at home.